EXPLORING THE WELL-BEING OF THE UNIVERSAL APOSTOLIC PREFERENCES OF ENGLISH EDUCATION STUDENTS AT PRIVATE CATHOLIC UNIVERSITY - Angelina, Patricia; Bram, Barli (IJIET (International Journal of Indonesian Education and Teaching), 2025)
This study aimed to investigate factors affecting the well-being of the students of the English Language Education Study Program of Sanata Dharma University, a private Catholic higher education institution. It also examined the students coping mechanisms to tackle stressors. This study used a survey method, and data were collected using an online questionnaire that consisted of open-ended questions which addressed the factors that affected the students well-being and their coping mechanisms. The participants were 70 students from Sanata Dharma University's English Language Education Study Program. Results showed the respondents faced seven factors which affected their well-being, namely academic stress, financial condition, social relationships, physical and mental health, time management, support system availability, and high expectations. The participants used seven coping mechanisms to maintain and improve their well-being as follows: having a healthy lifestyle, doing hobbies, socializing with new people, managing time well and setting priorities, knowing limits, doing independent study outside campus, and finding a support system.